Bone formation at posterolateral intertransverse lumbar fusion - Buyong, Zunariah; Zakaria@Mohamad, Zamzuri; Khalid, Kamarul Ariffin; Zulkifly, Ahmad Hafiz; Ab Rahman, Jamalludin; Abdul Wahab, Amran; Abdel Wahab, Emad Mohamad Nafie; Fazan, Fazilah (2010)
This study aimed to compare bone formation in posterolateral lumbar fusion after implantation with hydroxyapatite (HA) granules alone, HA granules mixed with autologous platelet rich plasma (HA-PRP) and autograft. Twenty-four New Zealand white rabbits were used. The rabbits were randomized into two groups of twelve rabbits each based on the graft materials used. All the rabbits underwent single level bilateral posterolateral intertransverse lumbar fusion between L5 and L6 segment of lumbar spines. One side of the animals was implanted with either HA alone or HA mixed with PRP. While the contra lateral side was implanted with autograft, and served as the control. The animals were sacrificed after six weeks post-implantation for undecalcified histological and radiological assessments. Results showed that the control group with autograft healed with a good fusion mass. Interestingly, HA granules only group healed with better bone formation than HA-PRP.